The Effect of Current Ratio, Debt to Equity Ratio, and Return on Assets on Dividend Policy Industrial Consumption Goods Sector Companies Listed in The Indonesian Stock Exchange Year 2013 – 2016 - Infante, Yusnita Octafilia Theresia A Yesu; Arlyana, Lely; Haristan, Meiviana; Akri, Peri (International Conference on Business Management and Accounting, 2024)
The aim of this study is to investigate and analyze the influence of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) on the Dividend Payout Ratio (DPR) of the consumer goods companies that have been listed in Indonesia Stock Exchange (IDX). The population of this study is thirty companies. Using the purposive sampling method, nineteen consumer goods companies were listed in the Indonesia stock exchange from 2013 to 2016 as the sample. In this study, the method of data analysis is used: descriptive analysis, Multiple Linear Regression Analysis, Test Assumptions Classical, F-test, Coefficient of Determination, and t-test. The result obtained by using regression concluded that CR, DER, and ROA do not influence DPR.